Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products and Services: Phase I: Caribbean: Country Report: Commonwealth of Dominica - Agrico (Technical Centre for Agricultural and Rural Cooperation, 2005)
This study commissioned by CTA aims to identify agricultural information needs of key actors / beneficiaries for CTA products and services, potential actors ..and, to develop some baseline data to facilitate subsequent monitoring activities.